LITHUANIAN RESOURCES AT SELECTED LIBRARIES, ARCHIVES, AND MUSEUMS IN THE UNITED STATES - BURCHINAL, LEE G. (Knygotyra, 2015)
Sudan American Foundation for Education, Inc.414 N. Henderson Road, Suite 1205Arlington VA 22202 USAE-mail: lee.burchinal@verizon.comThis paper describes the development of the online Directory of Lithuanian Resources at Selected Libraries, Archives, and Museums in the United States. Eighty-six potential sources of information about scholarly and non-scholarly printed materials as well as archival collections, museum artifacts, and audio-visual materials were identified from references in publications, previous surveys, and information obtained from Web sites of organizations. Based on available information, draft descriptions of the holdings or collections were prepared for 84 organizations and sent to them for verification andcorrection. Revised records for the 82 sources constitute the content of the Directory. The 82 sources contain an extensive and wide variety of materials, including large collections of books, serials, newspapers, and other materials in Lithuanian; substantial university and public library collections of Lithuanian-related materials; hundreds of named archives related to individuals, families, and groups; special collections of Lithuanian coins, military-related items, folk art, and memorabilia; and oral histories and films based on the experiences of Lithuanian émigrés.
Keywords: Lithuanian resources; printed materials; archival collections; museum artifacts; audio-visual materials